Preoperative Risk Factors Responsible For Conversion Of Laparoscopic Cholecystectomy To Open Cholecystectomy - Kumar, Krishna; Dabi, Kshatrapal; Mehta, Lokesh; Chitara, Kunal; Tambi, Suchi; Jinger, Shweta (Journal of Neonatal Surgery, 2025)
Background: Laparoscopic cholecystectomy is the standard surgical method for treating symptomatic gallstone disease. Despite advances in technique and experience, open cholecystectomy may be required in some cases to ensure patient safety. Identifying preoperative risk factors can aid in anticipating difficult surgeries and improving results. Objectives: The goal is to assess the incidence of conversion from laparoscopic to open cholecystectomy, as well as to identify preoperative clinical, laboratory, and radiological risk factors. Materials and Methods: Over the course of 18 months, 200 patients undergoing laparoscopic cholecystectomy at a tertiary care hospital participated in this prospective observational study. Preoperative characteristics such as age, gender, body mass index, history of acute cholecystitis, previous upper abdominal surgery, white blood cell count, and ultrasonographic results were documented. Conversion to open cholecystectomy was observed. Statistical analysis was conducted using chi-square test and multivariate logistic regression, with p-values <0.05 considered significant. Results: Out of 200 patients, 26 (13%) required an open cholecystectomy. Preoperative risk variables for conversion included age >60 years, male gender, acute cholecystitis, previous upper abdominal surgery, elevated white blood cell count, gallbladder wall thickness >4 mm, and pericholecystic fluid (p < 0.05). Acute cholecystitis and gallbladder wall thickening were found to be independent predictors on multivariate analysis. Conclusion: Certain preoperative factors considerably enhance the chances of converting from laparoscopic to open cholecystectomy. Early identification of these risk factors leads to better patient counseling, operative planning, and surgical outcomes